Erythrocyte Sedimentation Rate (ESR) and C-Reactive Protein (CRP) in COVID-19 patients at the RSPTN UNHAS, Makassar - Rosdiana Mus; Rahmat Aryandi Aryandi; Islawati Islawati; Titin Agustina (Diponegoro International Medical Journal, 2023)
Coronavirus Disease-19 (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) as part of the novel coronavirus. Clinical monitoring and appropriate treatment strategies are essential to reduce case fatality. Various examination parameters to support diagnosis such as ESR and CRP in assessing the response of a systemic inflammatory process. C-reactive protein (CRP) levels can be used in the initial diagnosis of pneumonia and patients with severe pneumonia have high CRP levels. Erythrocyte Sedimentation Rate (ESR) as a non-specific inflammatory response examination which has increased in various physiological disorders such as infection and inflammation. The purpose of this study was to determine the levels of ESR and CRP as biomarkers of inflammation in patients with COVID-19 at RSPTN UNHAS, Makassar. This study involved 32 subjects who met the inclusion criteria for positive RT-PCR COVID-19,  age 21-70 years and  signed of informed concent. Erythrocyte Sedimentation Rate Check by Auto ESR Analyzer using the Westergreen method and C-reactive protein Check by qualitative test.  The result of this research that the average age of the subjects was 51 years consisting of 14 (56.2%) female subjects and 18 (43.8%) male subjects. The median value of CRP examination is 48.00 mg/dL and the median value of ESR is 63.00 mm/hour. 2. There is a significant difference between the CRP values in male and female subjects. There is a significant relationship between CRP and ESR values with a strong